Interannual Variability of the Mid‐Atlantic Bight Cold Pool. Issue 8 (21st August 2020) - Chen, Zhuomin; Curchitser, Enrique N.
Abstract: The Mid‐Atlantic Bight (MAB) Cold Pool is a bottom‐trapped, cold (temperature below 10°C) and fresh (practical salinity below 34) water mass that is isolated from the surface by the seasonal thermocline and is located over the midshelf and outer shelf of the MAB. The interannual variability of the Cold Pool with regard to its persistence time, volume, temperature, and seasonal along‐shelf propagation is investigated based on a long‐term (1958–2007) high‐resolution regional model of the northwest Atlantic Ocean. A Cold Pool Index is defined and computed in order to quantify the strength of the Cold Pool on the interannual timescale. Anomalous strong, weak, and normal years are categorized and compared based on the Cold Pool Index. A detailed quantitative study of the volume‐averaged heat budget of the Cold Pool region (CPR) has been examined on the interannual timescale. Results suggest that the initial temperature and abnormal warming/cooling due to advection are the primary drivers in the interannual variability of the near‐bottom CPR temperature anomaly during stratified seasons. The long persistence of temperature anomalies from winter to summer in the CPR also suggests a potential for seasonal predictability. Plain Language Summary: The interannual variability of the Mid‐Atlantic Bight (MAB) Cold Pool is investigated based on a long‐term (1958–2007) high‐resolution regional numerical model of the northwest Atlantic Ocean. The Cold Pool is a relatively cold and fresh water mass that exists below the surface and is located over the mid‐shelf and outer‐shelf of MAB. A Cold Pool Index (CPI) is defined and computed based on its persistence time, volume, temperature, and seasonal along‐shelf propagation and is used to quantify the strength of the Cold Pool in different years. The Cold Pool years are then categorized as strong, weak, and normal years based on the CPI. A detailed quantitative heat budget study of the Cold Pool region (CPR) has been examined in order to expose the main drivers of the interannual variability. Results suggest that the initial winter‐time temperature and warming/cooling due to advection are the primary drivers in controlling the interannual variability of the near‐bottom CPR temperature during spring and summer. The long persistence of temperature anomalies from winter to summer in the CPR also suggests a potential for seasonal predictability of the Cold Pool. Key Points: The Cold Pool interannual variability regarding its persistence, volume, temperature, and propagation is investigated using a multidecadal numerical model A Cold Pool strength index is defined and used to identify extreme years Interannual variability of the near‐bottom Cold Pool temperature is controlled by initial winter temperature and total oceanic advection